Nerdcrush - Emrich, Alisha (New York : Running Press Kids, 2023)
Shy sixteen-year-old Ramona uses cosplay as a way to escape her shyness and feel seen, but when she emails her crush using her online persona, Rel, and he starts to fall for her, Ramona must decide whether to hide behind her character forever or take a chance and let her crush see the real her.
New YA Book 2023 Winter.
Ages 13+
Grades 7-9.
Keywords: Identity -- Fiction; Cosplay -- Fiction; Self-confidence -- Fiction; Love -- Fiction; African Americans -- Fiction; Electronic mail messages -- Fiction; Novels; Romance fiction